Workshop Peluang Usaha Di Bidang Olahraga Bagi Guru PJOK Kota Kupang - Michael Johannes Hadiwijaya Louk; Al Ihzan Tajuddin; Ronald Dwi Ardian Fufu; Fera Ratna dewi Siagian; Erwin S. Neolaka; I Nyoman Wahyu Esa Wijaya; Salmon Runesi; Lukas Maria Boleng; Jurdan Martin Siahaan (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2022)
Nowadays, the interest in sports, especially in game sports, is increasing among young people. It has become a habit, and they even feel uncomfortable when they don't play sports, such as futsal and basketball. In line with their increasing passion, the trend regarding sports accessories is also increasing day by day. Thus, more and more people want to show their "fashion" in sports. In addition to fashion, the development of sports in the field of advice and infrastructure is also increasing and over time there have been changes in both quality and form that suit the needs and abilities of athletes, so sports actors must provide the latest tools so that they can support ongoing training, for example takraw balls which are used to use rattan along with Over time, they changed to use plastic materials. The implementation of a business opportunity workshop in the field of sports on August 13, 2022 which was attended by 80 participants. Resource persons provide knowledge and experience on how to see business opportunities in the field of sports, participants also carry out and make designs and business proposals which are considered as business opportunities in the field of sports in the environment around which participants live. The challenge for sports graduates is the difficulty of finding work, through this workshop it is hoped that this will provide additional insight so that sports graduates do not only focus on teaching but can start businesses in the sports sector.